High Myostatin Serum Related with High Prevalence of Sarcopenia Among Elderly Population in Pedawa Village, Bali, Indonesia - I Gusti Putu Suka Aryana; I Nyoman Astika; Raden Ayu Tuty Kuswardhani; Ida Bagus Putu Putrawan; Ni Ketut Rai Purnami; Wayan Giri Putra; Anak Agung Wiradewi Lestari; I Nyoman Wande (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Sarcopenia is defined as a decrease in muscle mass accompanied by a decrease in muscle strength and performance. Sarcopenia arises from the disruption of the complex balance between anabolic and catabolic factors. Myostatin strongly influences muscle growth inhibition. Deletion and function loss of myostatin causes hyperplasia and skeletal muscle hypertrophy.METHODS: This study was an analytical cross-sectional study. Seventy respondents aged ≥60 years in Pedawa Village, Bali, Indonesia were selected by using the stratified random sampling technique. Sarcopenia status was assessed according to Asian Working Group for Sarcopenia (AWGS) criteria, including muscle mass, grip strength, and walking speed. While the myostatin serum levels was measured by enzyme-linked immunosorbent assay (ELISA).RESULTS: The incidence of sarcopenia in the elderly was 45 people (64.3%). Based on the analysis, there was a significant difference between myostatin levels in sarcopenia subjects (47.59 ng/mL) and non-sarcopenia subjects (39.7 ng/mL). Based on the statistical calculations, it was determined that the cut-off range of myostatin levels was 48.91 ng/mL. The prevalence ratio of sarcopenia incidence based on the myostatin levels in the elderly was 3.84, while based on the combination of age risk and myostatin levels was 9.75.CONCLUSION: Based of the data, there are significant differences of myostatin level between elderly people with and without sarcopenia. The prevalence of high myostatin levels in elderly is almost 4 times higher than low myostatin levels in the elderly.KEYWORDS: myostatin, sarcopenia, elderly